Contribuições para atualização do arcabouço legal estadual de ciência, tecnologia e inovação, com enfoque no estado do Amazonas - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
Updating the legal framework for science, technology and innovation is a very important step towards maintaining a regulatory environment favorable to the development of an innovation ecosystem that is capable of enhancing local vocations, successful ventures, innovative solutions, research and development, because when if there is legal security and stability, investments in S,T&I are better applied, ensuring that the State can advance towards a more sustainable and competitive economy with direct impacts on people's quality of life, increasing the generation of jobs and income and that can ensure all these advances for future generations. Given this context, the objective of this work was to develop a proposal for a process to update the S,T&I legal framework applied to the state of Amazonas. The methodology used was qualitative and with a comparative analysis of researched processes and official documents surveyed, such as Laws, Decrees, Normative Instructions, Ordinances and relevant Resolutions referring to similar laws of the Union and other States. In the end, as academic results, content was developed that can serve as a basis for society to have access to various information, providing the academic community, professionals in the sector and other actors with academic material with technical characteristics aimed at the updating process. Of the state legal framework for S,T&I that enables the construction and modernization of public policies for science, technology and innovation.
Contributions to updating the state legal framework for science, technology and innovation, focusing on the state of Amazonas
Keywords: Inovações tecnológicas - Política governamental - Amazonas; Ciência - Amazonas; Tecnologia - Amazonas; CIENCIAS SOCIAIS APLICADAS; Arcabouço legal; Política pública; Ciência; Tecnologia; Inovação; Amazonas; Legal framework; Public policy; Science; Technology; Innovation; Amazon